PRAGMATIC ANALYSIS OF STYLISTIC DEVICES IN ENGLISH AND UZBEK LANGUAGE TEACHING SYSTEM - Halima Karimova Polatvoy qizi (World Scientific Research Journal, 2025)
Abstract: integration of pragmatic analysis into the study and teaching of stylistic devices in both English and Uzbek language learning systems represents a modern approach, reflecting evolving priorities in communicative language teaching. Stylistic devices—instruments that enrich texts and verbal expressions by adding emphasis, suggestion, or a particular tone—are traditionally given considerable attention in literary analysis. However, their pragmatic dimension, particularly in the classroom context, remains underrepresented in language education methodologies. This article undertakes a deep exploration into how pragmatic principles shape the teaching, interpretation, and functional use of stylistic devices in English and Uzbek classrooms, and how such considerations can improve language proficiency and communicative competence.